Transformasi Pasar Tradisional Melati ke Pasar Monza: Perspektif Sosio-Ekonomi - Lestari, Indah; Sumantri, Pulung; Hardiyansyah, Muhammad Ricky (Medan Resource Center, 2025)
This study aims to (1) identify the background of the emergence of Monza traders in Melati Market, (2) analyze Monza trading activities in Melati Market, and (3) understand the socio-economic conditions of Monza traders in Melati Market. This research employs a qualitative approach with historical methods. Data collection techniques include observation, interviews, and document analysis, while data analysis is conducted through data reduction, triangulation, and conclusion drawing. The findings reveal that (1) Melati Market is well known for selling affordable, branded second-hand clothing and has undergone significant growth in recent years. (2) Monza traders’ activities in Melati Market involve preparing merchandise, arranging products, serving customers, and engaging directly in bargaining processes. Traders actively interact with buyers, offering their goods, explaining product quality and pricing, and assisting customers in selecting the best items. (3) The socio-economic conditions of Monza traders are reflected not only in their commercial transactions but also in their daily social interactions. The strong sense of community among traders fosters a harmonious trading environment, ensuring a safe and supportive atmosphere. Economically, Monza trading serves as the primary livelihood for these traders, enabling them to sustain their daily needs.